The right to safe and adequate transportation as a human right: A normative legal analysis of Indonesia’s public transportation system - Kharisma Mega Suryadewi (PT WIM Solusi Prima, 2026)
Public transportation constitutes a fundamental instrument in modern society, serving not merely as a means of mobility but also as a medium for fulfilling various constitutional rights of citizens. Access to education, healthcare, employment, and public services largely depends on the availability of safe, adequate, affordable, and non-discriminatory transportation systems. From a human rights perspective, transportation should not be viewed solely as an economic or infrastructural sector, but rather as part of the state's obligation to ensure human welfare and dignity. Although Indonesia has enacted various regulations governing public transportation, significant issues remain, including traffic accidents, limited accessibility for vulnerable groups, weak passenger protection mechanisms, and inadequate implementation of public service standards. This research aims to analyze the legal position of the right to safe and adequate transportation as a human right and to examine the effectiveness of Indonesia's transportation law system in protecting passengers' rights. Using normative legal research methods with statutory, conceptual, and human rights approaches, this study finds that the right to safe and adequate transportation possesses a strong constitutional foundation within Indonesia's legal system despite not being explicitly recognized as a separate right. The state bears obligations to respect, protect, and fulfill this right through regulatory frameworks, supervision, and quality transportation services. However, a gap remains between legal norms and practical implementation. Therefore, a stronger human rights-based transportation paradigm is required within national transportation development.